Developments of CO2-emissions and costs for small electric and combustion engine vehicles in Germany. (May 2015) - Bickert, Stefan; Kampker, Achim; Greger, Dennis
Highlights: Total emissions can be saved by BEV even with low annual driving distances. Production emissions of BEV exceed production emissions of ICE. Today, private costs of BEV exceed private costs of ICE. External costs are high, but cannot provide an economic advantage for BEV today. Abstract: Electric vehicles have the potential to lower emissions in the mobility sector, but especially high costs might hinder their market development. This paper aims to access environmental and economic impacts and potentials by comparing CO2 -emissions and costs of small vehicles. Considering actual data it is analysed, if and under which conditions electric vehicles are financially competitive for private consumers and under which conditions emissions can be saved. For this, a multiple-stage approach is focusing on (1) emissions during production and operation, (2) private costs and (3) external costs of emissions. A model of total cost of ownership is applied for the analysis of private and external costs. Results show that emissions of electric vehicles exceed emissions of combustion engine vehicles in the production phase, but electric vehicles cause fewer emissions during operation. Total emissions can be saved by electric vehicles even with low annual driving distances (2500–5500 km/a today). Results highly depend on the form of electricity production. Today, private costs of electric vehicles exceed the costs of combustion engine vehicles. Due to cost decreases electric vehicles can gain financial advantages in the future. External costs are high, especially for combustion engine vehicles (up to 15% of private costs), but in none of the considered cases high enough to give electric vehicles a financial advantage today. This picture will change in the future.